Fair rosaline eaudiobook - Solomons, Natasha (Recorded Books Inc., 2023)
A shattering untelling of Romeo and JulietThe first time Romeo Montague sees young Rosaline Capulet he falls instantly in love. Rosaline, headstrong and independent, is unsure of Romeo's attentions, but with her father determined that she join a convent, this handsome and charming stranger offers her the chance of a different life.Soon though, Rosaline begins to doubt all that Romeo has told her. She breaks off the match, only for Romeo's gaze to turn towards her cousin, thirteen-year-old Juliet. Gradually, Rosaline realizes that it is not only Juliet's reputation at stake but her life. With only hours remaining before she will be banished behind the nunnery walls, will Rosaline save Juliet from her Romeo? Or can this story only ever end one way?This audiobook includes an exclusive author and narrator Q&A.